Application of Electrical Conductivity Measurements in Material Research and in Solution of Technological Problems - Ocenasek, Vladivoj; Lustinec, Jan; Cieslar, Miroslav; Bajcura, Matus (Manufacturing Technology Journal, 2018)
Electrical conductivity depends significantly on a structural state. It can be influenced by chemical composition, content of alloying elements, presence of different types of phases and dislocation substructure as well. Therefore, the relation between electrical conductivity and mechanical properties is very interesting from a material point of view. In combination with structural analyses (metallography, electron microscopy), important information about materials structures and their changes as a function of various factors (deformation, heat treatment) can be obtained. The present paper describes the role of electrical conductivity measurements during an investigation of the effect of technological parameters on the structure and properties of aluminium alloys.
Keywords: electrical conductivity; aluminium alloys; heat treatment; production technology